Black Box Testing pada Website Sistem Perpustakaan Menggunakan Metode Equivalence Partitioning dan Analisis Boundary Value - Restu Langit, Muhammad Shandy; Voutama, Apriade; Ali Ridha, Azhari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2024)
The most important stage when developing a system is testing. Testing on the system needs to be carried out in order to find out how far the usability of the system is working. This research aims to carry out blackbox testing on the library system website by utilizing the Boundary Value and Equivalence Partitioning analysis methods to understand whether the functions on the website are running properly and to evaluate the suitability of website features with user needs. This test is carried out on the main function of the website, namely the login and sign in menu. This black box test is to test the accuracy of the type of input data and data entered into the system. Based on testing using this method, the results obtained were that no functional errors were found on the input side of the system and no errors were identified on the website system of the Bekasi Regency Archives and Library Service.